Propostas Curriculares Para o Ensino Médio (1998/2013): uma análise sob a ótica de Jürgen Habermas - Scarlatto, Elaine Cristina [UNESP] (2015)
The goal of this thesis is to analyze the possibilities of sociocultural and political formation of High School students, being this formation understood by the perspective of the Critical Theory idea, particularly from Jürgen Habermas. This is a theoretical research from qualitative nature whose documental sources are: 1) Parâmetros Curriculares Nacionais para o Ensino Médio (PCNEM Brazilian Curricular Parameters for Secondary Education) and the Orientações Complementares (+PCNEM Additional Guidelines), specially for Humanities disciplines, their theoretical assumptions and proposals for a new educational practice; 2) New Curricular Guidelines for Basic Education, for Secondary Education; Programa Ensino Médio Inovador (PROEMI High School Program Innovator); 3) Papers from Comissão Nacional para a Reformulação do Ensino Médio (CEENSI National Committee for Secondary Education Reformulation) from Chamber of Deputies, contending the guidelines for State Seminaries for Innovator Proposals for this level of education; 4) Laws on processing of approval to reformulate Secondary Education. We also consider the civil society's manifestations - private foundations, researchers, experts and associations of teachers - about the mandatory changes on High School Syllabus. Assuming that in High School ones begin to acquire sociocultural and political formation focused on the valorization and defense of ideals of the democracy, this work intend to expose that besides all the advances the new curricular proposals do not contribute or contributes poorly for that formation and those proposals, in case of approval, for lacking clarity and precision on their formative goals, will not be enough to overcome the instrumental rationality that prevails on this Secondary Education formation. Therefore, the need of a syllabus based on the rationality of the communicative action, proposed by J. Habermas, considering contribute to a formation that...